Characteristics of the Enterococcus Phage vB_EfS_SE, and the Properties of Its Chimeric Endolysins Harboring a PlySE-Carbohydrate-Binding Domain and a Synthetic Enzymatic Domain - Rustam M. Buzikov; Vladislav A. Kulyabin; Olga N. Koposova; Vyacheslav A. Arlyapov; Andrey M. Shadrin (MDPI AG, 2024)
Background/Objectives: The World Health Organization has selected enterococci as one of the priority multidrug-resistant microorganisms for the development of new antibacterial drugs. Bacteriophages are promising antibacterial agents, but the biology of bacteriophages requires deeper understanding. Methods: The vB_EfS_SE phage which is capable of infecting four species of the genus Enterococci was isolated from sewage plant. The complete genome of the vB_EfS_SE phage was sequenced using illumina technology. The endolysin gene was cloned into pBAD18 expression vector. Two chimeric endolysins were engineered using the vB_EfS_SE carbohydrate-binding domain (CBD) and replacing its enzymatically active domain (EAD). Results: The bacteriophage exhibits promising lytic properties and persists at temperatures of 40 °C and below, and under pH conditions ranging from 5 to 11. The genome sequence is 57,904 bp in length. The vB_EfS_SE endolysin PlySE and chimeric endolysins PlyIME-SE and PlySheep-SE were found to have the same range of specificity, but different thermostability properties and a different pH range for enzyme activity. Conclusions: Taking together the results obtained in this work and other published studies, we can highly appreciate the potential of Saphexavirus phages and their endolysins as novel antibacterial compounds.